2013
DOI: 10.1111/ffe.12085
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on rotatory bending fretting fatigue damage of railway axles

Abstract: Fretting damage failure analysis of a Chinese carbon railway axle RD2 was carried out. The wheel hub was in situ cut to expose the damaged surface of the wheel seat to avoid additional damage. A small‐scale axle test rig was developed, and simulation tests were performed at different rotator speeds of 1800 and 2100 rpm. The wear mechanism of fretting damage areas was a combination of abrasive wear, oxidative wear and delamination. The fracture surfaces exhibited characterization of multisource and step‐profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 24 publications
5
31
0
Order By: Relevance
“…For the press-fitted shaft/flange joint at 1:3 scale, the maximum stress in the area of the critical wheel seat/axle body transition point was up to 2.5 times higher in the surface induction-hardened specimens than in the standard specimens with no surface heat treatment when subjected to the same number of cycles (Table 5). This result is in accordance with the results published by Makino et al 3 which show induction hardened S38C steel axles tempered at 200°C (used in Shinkansen trains) attaining fatigue limits in the range 270-300 MPa in the area of the press-fitted joint for 10 7 cycles.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…For the press-fitted shaft/flange joint at 1:3 scale, the maximum stress in the area of the critical wheel seat/axle body transition point was up to 2.5 times higher in the surface induction-hardened specimens than in the standard specimens with no surface heat treatment when subjected to the same number of cycles (Table 5). This result is in accordance with the results published by Makino et al 3 which show induction hardened S38C steel axles tempered at 200°C (used in Shinkansen trains) attaining fatigue limits in the range 270-300 MPa in the area of the press-fitted joint for 10 7 cycles.…”
Section: Discussionsupporting
confidence: 93%
“…Demands for higher reliability and safety of railway vehicles have brought intensive research of degradation processes in railway wheelsets and new approaches to wheelset design . Extremely high repeated contact stresses between wheels and rails cause rolling contact fatigue .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4,5] Fatigue fracture impaired the security of the high-speed railway. [6][7][8][9] Moreover, previous studies showed that the forging process affected the grain size, second-phase particle size, and mechanical properties. [10][11][12][13] Song et al [9] indicated that the inclusions at the subsurface were most harmful to fatigue performance.…”
Section: Introductionmentioning
confidence: 99%